Immune Responses Against Classical Swine Fever Virus: Between Ignorance and Lunacy - Summerfield, Artur; Ruggli, Nicolas (Frontiers in Veterinary Science, 2015)
Classical swine fever virus infection of pigs causes disease courses from life-threatening to asymptomatic, depending on the virulence of the virus strain and the immunocompetence of the host. The virus targets immune cells which are central in orchestrating innate and adaptive immune responses such as macrophages and conventional and plasmacytoid dendritic cells. Here we review current knowledge and concepts aiming to explain the immunopathogenesis of the disease at both the host and the cellular level. We propose that the interferon type I system and in particular the interaction of the virus with plasmacytoid dendritic cells and macrophages is crucial to understand elements governing the induction of protective rather than pathogenic immune responses. The review also concludes that despite the knowledge available many aspects of classical swine fever immunopathogenesis are still puzzling.